Correio Paulistano: o primeiro diário de São Paulo e a cobertura da Semana de Arte Moderna - O jornal que não ladra, não cacareja e não morde" - Thalassa, Ângela (2007)
The current research looking for to comprehend Correio Paulistano newspaper (1854-1963) first daily of São Paulo and third in Brazil and its relation with modernist movement showed by the comparison between their articles published and other published by their competing newspapers. Correio Paulistano and other newspapers were chosen for such analysis as O Estadão, Jornal do Commércio, A Gazeta and Folha da Noite (currently Folha de São Paulo). The chosen articles could prove that Correio Paulistano was the unique one that gave favorable coverage to the event recognizing the avant-garde of modernist movement and went against to the elite and the press at that time which considered the movement as subversives of art and silly and cretin spirits or devilish futurists . Besides at that time Correio Paulistano was the newspaper of representative of São Paulo Republican Party which was directed and financed by aristocracy and traditionalist and nostalgic people. The discovering of Menotti Del Picchia outstanding presence in editorial staff or Helios as he used to sign the principal article entitle Chronica Social and that was stage of his literary and convincing journalism practice was fundamental to understanding some gross keynote differences in coverage of 22 Week which could be pointed as one of polemical cases that didn t receive a manipulated approach by a press that historically use to work closing in pool. Such conflict just was possible because this mentioned Correio Paulistano position. This newspaper arose during monarchical period and was republican by conviction sometimes liberal sometimes conservative. It was rebel against political influenced forces and kept against position face to Vargas government and was been slapsticked during several years by these government forces. The support to the Modernist Movement was considered an extra rebelliousness in this conservative Correio Paulistano tumultuous life. Our object is approached as part of our journalism historical memory recovering when we consider Correio Paulistano as shadow and reflection of important political and social changes which culminated in the current society and press. As instrument for the developing of this reasearch could be consider the incursion of authors as Nelson Werneck Sodré, Juarez Bahia, Paulo Duarte, Alberto de Souza (press), Mário da Silva Brito, Francisco Alambert e Charles Harrison (Modernism), José Maria Bello, Lilia Schwarcz and Leonardo Trevisan (History). In critical sense formation referring to the communicational processes which can be visible in the research trajectory we can named authors Paul Virilio, Eugênio Trivinho, Krishan Kumar, Harry Pross, James Hillmann, Edgar Morin, Vilém Flusser, Jean Baudrillard, Boris Cyrulnik and Norval Baitello